Peran Lembaga Musik Pervagatus sebagai Band Performer dalam Membentuk Respresentasi Musik pada Program TV One Damai Indonesiaku - Keisya Amanda Putri; Adelia Dwi Ratri; Tria Patrianti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study investigates how Lembaga Musik Pervagatus, a group that does not display Islamic identity, creates an Islamic musical image when performing at religious events in Islamic campuses. This study investigates how visual elements, song selection, and stage interaction influence audience perception. It does so using qualitative methods through interviews and performance observations. How the band's performative identity is influenced by attributes such as appearance, personality, cultural values, and audience relations is studied using Kapferer's Brand Identity Prism model. Conversely, Stuart Hall's theory of representation helps explain how Islamic meaning emerges in the context of events. The results show that the image of Islamic music attached to Pervagatus does not originate from the band's original identity; rather, it is a construction of meaning influenced by the context of religious events and the audience's interpretation of the song ‘Maulana Ya Maulana’ that they performed. This perception was further reinforced by their neat, polite, and enthusiastic appearance. The results show that the relationship between performance, context, and audience interpretation shapes the image of Islamic music on campus.